Assessment of a developed pig cadaver model for teaching crown lengthening surgical procedures - Zhong, Jinsheng; Shi, Dong; Wang, Cui; Zhen, Min; Wei, Yiping; Han, Ziyao; Hu, Wenjie; Chung, Kwok-Hung (PeerJ, 2022)
Background Information regarding using a pig cadaver model for teaching purposes in dentistry is limited, especially for periodontal surgery procedures. The aim of this study was to assess the feasibility and efficacy of teaching crown lengthening surgical procedures using a prepared pig cadaver model. Methods Mandibles of slaughtered pigs with subgingival crown fracture defects on two premolars and two molars on each side were prepared as periodontal surgery teaching cases. A resident group (n = 20) and an instructor group (n = 18) participated in assessing the efficacy of the model by completing questionnaires before and after training sessions. Data was either assessed descriptively or analyzed statistically with Wilcoxon signed-rank test with the significance level at α = 0.05. Results Results revealed that all the knowledge points showed statistically significant improvements (p < 0.05) except for the procedure to determine the quantity of bone removal during osteotomy procedures. Most residents rated the efficacy of the model obtained with 9.0 out of 10 scale. The data of effectiveness of the pig cadaver model from the instructor group ranged from 7.4 ± 1.4 to 9.0 ± 1.0. Conclusion Results of this study support feasibility in using prepared pig cadaver models to teach crown lengthening surgical procedures to postgraduates.
Keywords: Crown lengthening surgery; Animal model; Dental education